Nickel-based positive electrode material and preparation method thereof

By using a three-layer coating and alkaline washing process, the problem of surface structure damage in high-nickel cathode materials during water washing was solved, achieving a high lithium-ion diffusion rate and a stable crystal structure, thereby improving the cycle stability and electrochemical performance of the material.

CN120998981APending Publication Date: 2025-11-21HUNAN SHANSHAN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511227717.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

The surface structure of high-nickel cathode materials is damaged during water washing, resulting in lithium defects and high impedance, which affects cycle stability and electrochemical performance.

Method used

A three-layer coating structure is adopted, including a first coating layer, a second coating layer and a third coating layer, which are respectively composed of at least one of the fourth-period variable-valence transition metal elements, Li, Na, K and Al, and low-melting-point oxides. Combined with alkaline washing and dry coating processes, a stable layered structure is formed, which suppresses side reactions and lattice distortion caused by lithium ion insertion/extraction.

Benefits of technology

It improves the lithium-ion diffusion rate, stabilizes the material structure, reduces side reactions, and enhances the material's cycle stability and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120998981A_ABST
    Figure CN120998981A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of battery materials, and discloses a nickel-based positive electrode material which comprises a nickel-based positive electrode material matrix and three coating layers, the first coating layer coats the surfaces of primary particles and secondary particles of the nickel-based positive electrode material matrix, and coating elements comprise fourth-period variable-valence transition metal elements; the second coating layer is coated on the first coating layer, and coating elements comprise at least one of Li, Na, K and Al; the third coating layer is coated on the second coating layer, and the coating agent is an oxide with a melting point of less than 700 DEG C. The invention also discloses a preparation method, and alkali washing, wet coating and dry coating processes are combined to form a layered structure with high crystallinity inside and ordered crystal lattices and three stable coating layers on the surface. The nickel-based positive electrode material has a stable crystal structure and a low-impedance surface, has a relatively high lithium ion diffusion rate, also has a uniform surface coating layer, and can inhibit side reaction with an electrolyte in a circulation process.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of battery materials, and particularly relates to a positive electrode material and a preparation method thereof. BACKGROUND

[0002] With the rapid growth of the electric vehicle market, there is an increasing demand for lithium-ion batteries with high energy density, long life and low cost. In these batteries, the positive electrode material is one of the key factors determining the performance of the battery, and high-nickel positive electrodes have high specific capacity and cost-effectiveness, which are undoubtedly a strong driving force for high-energy-density lithium batteries. However, the lithium impurities remaining on the surface of high-nickel materials can cause more serious side reactions at high pressure, leading to rapid degradation of the material, internal strain accumulation and particle fracture during the cycling process of the battery, which poses challenges in terms of cycle stability and durability.

[0003] To solve the above problems existing in high-nickel positive electrode materials, the production process of traditional high-nickel ternary positive electrode materials currently adopts a water washing process, using water as the washing liquid. However, since high-nickel ternary positive electrode materials are sensitive to moisture, during the water washing process, the residual alkali on the surface of the substrate dissolves in water. Due to the difference in pH value between the substrate and water, a lithium concentration difference is formed between the inside and the surface of the substrate, leading to further precipitation of active lithium inside the substrate, destruction of the surface structure of the substrate, and a large number of lithium defects. Over-washing can cause lattice lithium to precipitate on the surface of the material substrate, resulting in a high content of divalent nickel on the surface, leading to the formation of high-impedance rock salt phases, and destruction of the surface structure of the material. At the same time, since the high-nickel ternary positive electrode material has a high nickel content, the side reaction with the electrolyte during the charging and discharging process is more serious, leading to high surface impedance and poor cycle performance, which affects the electrochemical performance of the high-nickel positive electrode material. SUMMARY The technical problem to be solved by the present application is to overcome the deficiencies and defects mentioned in the background art, and to provide a nickel-based positive electrode material and a preparation method thereof.

[0004] To solve the above technical problems, the technical solution proposed by the present application is as follows: A nickel-based positive electrode material, comprising a nickel-based positive electrode material substrate and a three-layer coating layer, a first coating layer coated on the surface of the primary particles and secondary particles of the nickel-based positive electrode material substrate, the coating element comprising a fourth period variable valence transition metal element; a second coating layer coated on the surface of the first coating layer, the coating element comprising at least one of Li, Na, K and Al; and a third coating layer coated on the surface of the second coating layer, the coating agent being an oxide with a melting point <700℃.

[0005] Preferably, the nickel-based positive electrode material has an average valence of Ni element on the surface of +2.6 to +2.9 through X-ray photoelectron spectroscopy (XPS) test; the nickel-based positive electrode material has a difference of 2θ angle position of 108 and 110 peaks in X-ray diffraction (XRD) spectrum ≥0.25°; during the charging process, the cell parameter c in the c-axis direction changes at a rate of Δc / c max ≤4%, wherein Δc is the change value of cell parameter c, and Δc=c max -c min .

[0006] Preferably, the coating element of the first coating layer comprises at least one of V, Mn, Fe, Co and Ni; the coating element of the third coating layer comprises at least one of B, Se, Co, Mn, Sb and V; the mass of the first coating layer is 0.5% to 3% of the mass of the nickel-based positive electrode material substrate, the mass of the second coating layer is 0.01% to 0.2% of the mass of the nickel-based positive electrode material substrate, and the mass of the third coating layer is 0.1% to 1% of the mass of the nickel-based positive electrode material substrate.

[0007] Preferably, the chemical formula of the nickel-based positive electrode material substrate is Li z Ni 1-x-y Co x M y O2, wherein M is at least one of Mn and Al, 1.0≤z≤1.03, 0≤x≤0.2, and 0≤y≤0.2.

[0008] Preferably, the content of lithium carbonate on the surface of the nickel-based positive electrode material is ≤0.3%, the content of lithium hydroxide is ≤0.6%, and the ratio of lithium to transition metal Li / Me is 1.0 to 1.01.

[0009] As a general technical concept, the application also provides a preparation method of the nickel-based positive electrode material, comprising the following steps: S1, mixing a nickel-based hydroxide precursor and a lithium source, and then performing sintering treatment to obtain a primary sintering product; S2, mixing the primary sintering product in step S1 with a first coating agent, and then performing sintering treatment after mixing to obtain a secondary sintering product; S3, preparing a second coating agent into an alkali solution, and then washing the secondary sintering product in step S2 with the alkali solution, and drying to obtain a washed product; S4, mixing the washed product in step S3 with a third coating agent, and then performing sintering treatment after mixing to obtain a nickel-based positive electrode material.

[0010] In the preparation method, preferably, in step S1, the lithium source comprises at least one of lithium hydroxide, lithium carbonate and lithium nitrate, and the molar ratio of lithium in the lithium source to the nickel-based hydroxide precursor is (1.03-1.08):1; the nickel-based hydroxide precursor is a nickel-cobalt-manganese, nickel-cobalt-aluminum or nickel-cobalt-manganese-aluminum hydroxide precursor; in step S2, the first coating agent is a hydroxide containing at least one of V, Mn, Fe, Co and Ni; in step S4, the third coating agent is an oxide containing at least one of B, Se, Co, Mn, Sb and V. In the preparation method, preferably, in step S1, the sintering treatment comprises two-stage sintering, the first-stage sintering has a sintering temperature of 450-600 DEG C and a holding time of 2-5 h, and the second-stage sintering has a sintering temperature of 600-800 DEG C and a holding time of 8-20 h; in step S2, the sintering treatment has a sintering temperature of 500-700 DEG C and a holding time of 4-10 h; in step S4, the sintering treatment has a sintering temperature of 300-700 DEG C and a holding time of 4-10 h; and the sintering atmosphere is an oxygen-containing atmosphere with an oxygen concentration of not less than 96%.

[0011] In the preparation method, preferably, in step S3, the second coating agent is an alkali solution prepared from at least one of NaAlO2, Na2CO3, NaOH, LiOH and KOH; the concentration c is 0.01-0.2 mol / L, the pH value is 10-13, the solubility s at 20 DEG C is greater than 1 g / 100 g water; the water washing temperature is 5-25 DEG C, the water washing solid-liquid mass ratio is 0.5-3.0, and the stirring speed during water washing is 400-900 rpm / min.

[0012] More preferably, before water washing, the surface lithium carbonate content t of the secondary sintering product is 0.3%-0.6%, the lithium hydroxide content h is 0.3%-0.8%, the solute relative molecular mass of the alkali solution is M, the maximum concentration cmax of the alkali solution is [1-100l(t-0.1%) / 1.43-100l(h-0.3%) / 10.8]x10s / M. The calculation method of the alkali solution concentration c is as follows: first, the water amount required for washing off the residual lithium on the surface of the substrate is calculated, then the total water amount is calculated according to the solid-liquid ratio, the difference between the two is the mass of the alkali solution, and finally the solute mass can be obtained according to the solubility, and the required alkali solution concentration can be obtained according to the solute mass and the total water amount. Through this method, the water washing intensity and the wet coating amount can be customized and designed, and the suitable water washing process parameters can be obtained.

[0013] Compared with the prior art, the present application has the following beneficial effects: 1. The nickel-based positive electrode material of the present application has a high lithium ion diffusion rate in the charging and discharging process through a stable crystal structure and a low impedance surface, can relieve the lattice distortion (C-axis direction) caused by lithium ion deintercalation, stabilize the crystal structure of the material, and through a uniform surface coating layer, establish lithium ion channels while protecting the material surface, inhibit the side reaction with electrolyte in the cycle process, reduce the generation of nickel oxide phase of high nickel components on the surface of high nickel material in the cycle process, and greatly improve the cycle stability of the material.

[0014] 2. The nickel-based positive electrode material of the present application combines alkali washing, wet coating and dry coating processes to form an internal high crystallinity and lattice-ordered layered structure and a surface three-layer stable coating layer, wherein the first coating layer connects the transition metal layer through a transition metal variable element on the surface of the primary particles to form a surface low impedance layered structure solid solution layer, improve the lithium ion transmission speed, reduce the surface nickel content while participating in the redox reaction, and stabilize the crystal structure; the second coating layer forms a thin and uniform coating layer between the grain boundaries of the primary particles as a pillar in the grain boundary to relieve the intergranular stress and protect the surface of the primary particles; and the third coating layer forms a uniform coating layer (lithium ion conductor coating layer) on the surface of the substrate through low-melting-point compound melting and sintering, establishes lithium ion transmission channels while protecting the material surface and inhibiting the side reaction with electrolyte.

[0015] 3. The water used in the conventional water washing process as a washing liquid, in the water washing process, with the residual alkali on the surface of the substrate dissolved in water, due to the difference in pH value between the substrate and water, lithium concentration difference is formed between the inside and the surface of the substrate, leading to further precipitation of active lithium in the inside of the substrate, surface structure damage of the substrate, and a large number of lithium defects. The nickel-based positive electrode material of the present application, according to the surface residual lithium of the positive electrode material substrate, dissolves an appropriate solubility alkali additive in water as a washing liquid, while controlling the water washing process (alkali concentration, solid-liquid ratio, pH value), on the one hand, realizes quantitative removal of residual lithium, ensures that the surface residual lithium of the substrate is removed while inhibiting the formation of surface lithium-deficient phase caused by lithium precipitation of the substrate in the conventional water washing process, avoids damage to the surface of the substrate, and can improve the valence state of surface nickel, reduce the generation of divalent nickel and rock salt phase, thereby forming a stable layered structure with good crystallinity from the inside to the outside, on the other hand, realizes quantitative wet coating, protects the substrate material, and further improves the cycle stability of the material. BRIEF DESCRIPTION OF DRAWINGS

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a SEM image of the nickel-based cathode material from Example 1.

[0018] Figure 2 The image shows the EPMA diagram of Co in the nickel-based cathode material of Example 1.

[0019] Figure 3 The image shows the EPMA diagram of Na in the nickel-based cathode material of Example 1.

[0020] Figure 4 The image shows the EPMA diagram of Al in the nickel-based cathode material of Example 1.

[0021] Figure 5 The image shows the EPMA diagram of element B in the nickel-based cathode material of Example 1.

[0022] Figure 6 The image shows the XPS plot of the nickel-based cathode material in Example 1.

[0023] Figure 7 The graph shows the relationship between cell parameter c and voltage during the charging process of the nickel-based cathode material in Example 1. Detailed Implementation

[0024] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0026] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0027] In the following embodiments, the rate of change of the unit cell along the c-axis is Δc / c max Where Δc is the change in the unit cell parameter c, Δc = c max -c min c max c minThe maximum and minimum of the cell parameters in the c-axis direction, respectively.

[0028] Example 1: A nickel-based positive electrode material, chemical formula is Li 1.0 Ni 0.91 Co 0.050 Mn 0.040 Na 0.001 Al 0.001 B 0.01 O2, wherein Co is a first coating layer element, Na and Al are second coating layer elements, and B is a third coating layer element. The first coating layer is coated on the surface of the primary particles and the secondary particles of the nickel-based positive electrode material matrix, the second coating layer is coated on the first coating layer, and the third coating layer is coated on the second coating layer. The average valence state of nickel on the surface of the positive electrode material is 2.82 by XPS test; the 2θ angle position difference of the 108 and 110 peaks in the XRD diffraction pattern is 0.42°; the c-axis cell change rate is 2.59% during the charging process by in-situ XRD test.

[0029] The preparation method of the above nickel-based positive electrode material comprises the following steps: (1) A nickel-cobalt-manganese hydroxide precursor Ni 0.93 Co 0.03 Mn 0.04 (OH)2, and lithium monohydrate are added into a high-speed mixing stirrer in a molar ratio of 1:1.05, stirred at a speed of 1000 rpm for 30 min, then heated to 500℃ at a heating rate of 3℃ / min in a box-type furnace with an oxygen concentration ≥96%, and then heated to 745℃ for 12 h, and then naturally cooled to room temperature, crushed, and sieved through a 300-mesh screen to obtain a primary sintered material; (2) The primary sintered material and Co(OH)2 are added into a high-speed mixing stirrer in a molar ratio of 1:0.02, stirred at a speed of 1000 rpm for 30 min, then heated to 650℃ at a heating rate of 3℃ / min in a box-type furnace under an oxygen atmosphere, and then naturally cooled to room temperature, and then sieved through a 300-mesh screen to obtain a secondary sintered material; (3) A 0.03 mol / L NaAlO2 solution is prepared with water, and the pH value is 11.78. The secondary sintered material obtained in step (2) is washed with the NaAlO2 solution for 3 min, the solid-liquid mass ratio of the washing is 0.9, the temperature of the deionized water for washing is controlled at 8℃, the stirring rate is 700 rpm, after washing, the sample is placed in a vacuum oven and vacuum dried at 160℃ for 6 h, and then naturally cooled to room temperature, and then sieved through a 300-mesh screen to obtain a water-washed product; (4) The water washing product and boric acid are added into a high-speed mixing stirrer in a proportion of 1:0.01 (molar ratio), stirred at a speed of 1000 rpm for 30 min, then heated to 300°C at a heating rate of 3°C / min in a box furnace under an oxygen atmosphere, and kept at 300°C for 6 h, naturally cooled to room temperature, screened through a 300-mesh screen, to obtain a nickel-based positive electrode material, an electron microscope image of which is shown in Figure 1 , an EPMA image is shown in Figures 2 to 5 , an XPS image is shown in Figure 6 , and a c-axis change graph of in-situ XRD testing is shown in Figure 7 .

[0030] As can be seen from Figure 1 , the material obtained in this embodiment has a loose and porous secondary spherical morphology; As can be seen from Figures 2 to 5 , the material has many internal pores, Co elements in the first coating layer are coated on the surface of primary particles and secondary particles of the nickel-based positive electrode material substrate, Al and Na elements in the second coating layer are coated on the surface of the primary particles (entering the secondary sphere along the gap between the primary particles during the alkali washing process, forming point-like coating at the grain boundaries), and are point-like coated on the surface of the first coating layer; B elements in the third coating layer are uniformly coated on the surface of the primary particles and the secondary sphere, and are coated on the surface of the second coating layer; As can be seen from Figure 6 , the peak area of trivalent nickel is higher than that of divalent nickel, the average valence of surface nickel is calculated to be 2.82, the content of divalent nickel on the surface is relatively small, indicating that the surface structure of the material is relatively stable, and the damage of the water washing process to the surface structure is inhibited; As can be seen from Figure 7 , during the first charging process, the lattice parameter c first increases and then decreases, and the change rate of c is 2.59% during the whole process, which indicates that the crystal structure of the material is stable and ordered, and the lattice distortion caused by lithium ion extraction is relieved; The content of lithium carbonate on the surface of the nickel-based positive electrode material is 0.073%, the content of lithium hydroxide is 0.469%, and the ratio of lithium to transition metal Li / Me is 1.002.

[0031] Example 2: A nickel-based positive electrode material, the chemical formula of which is Li 1.0 Ni 0.91 Co 0.050 Mn 0.040 Na 0.003 B 0.01O2, wherein, Co is a first coating layer element, Na is a second coating layer element, and B is a third coating layer element. The first coating layer is coated on the surface of the primary particles and the secondary particles of the nickel-based positive electrode material substrate, the second coating layer is coated on the first coating layer, and the third coating layer is coated on the second coating layer. The positive electrode material is subjected to XPS testing, the average valence of nickel on the surface is 2.71, the 2θ angle position difference of the 108 and 110 peaks in the XRD diffraction pattern is 0.38°, and the cell change rate in the c-axis direction during the charging process is 3.15% in the in-situ XRD testing.

[0032] The preparation method of the nickel-based positive electrode material includes the following steps: (1) A nickel-cobalt-manganese hydroxide precursor Ni 0.93 Co 0.03 Mn 0.04 (OH)2 and lithium monohydrate are added into a high-speed mixing stirrer in a molar ratio of 1:1.05, stirred at a speed of 1000 rpm for 30 min, then heated to 500℃ at a heating rate of 3℃ / min in a box-type furnace with an oxygen concentration of ≥96%, and then heated to 745℃ for 12 h, naturally cooled to room temperature, crushed, and sieved through a 300-mesh sieve to obtain a primary sintered material; (2) The primary sintered material and Co(OH)2 are added into a high-speed mixing stirrer in a molar ratio of 1:0.02, stirred at a speed of 1000 rpm for 30 min, then heated to 650℃ at a heating rate of 3℃ / min in a box-type furnace under an oxygen atmosphere, naturally cooled to room temperature, and sieved through a 300-mesh sieve to obtain a secondary sintered material; (3) A 0.05 mol / L Na2CO3 solution is prepared with water, and the pH value is 11.31. The secondary sintered material obtained in step (2) is washed with the Na2CO3 solution for 3 min, the solid-liquid mass ratio of the washing is 1.0, the temperature of the deionized water for washing is controlled at 8℃, the stirring rate is 700 rpm, the sample is placed in a vacuum oven after washing, vacuum dried at 160℃ for 6 h, then naturally cooled to room temperature, and sieved through a 300-mesh sieve to obtain a water-washed product; (4) The water-washed product and boric acid are added into a high-speed mixing stirrer in a molar ratio of 1:0.01, stirred at a speed of 1000 rpm for 30 min, then heated to 300℃ at a heating rate of 3℃ / min in a box-type furnace under an oxygen atmosphere, naturally cooled to room temperature, and sieved through a 300-mesh sieve to obtain a nickel-based positive electrode material.

[0033] The surface lithium carbonate content of the nickel-based positive electrode material is 0.070%, the lithium hydroxide content is 0.499%, and the lithium to transition metal ratio Li / Me is 1.004.

[0034] Example 3: A nickel-based positive electrode material, chemical formula is Li 1.0 Ni 0.91 Co 0.050 Mn 0.040 Na 0.001 Al 0.001 Se 0.002 O2, wherein Co is a first coating layer element, Na and Al are second coating layer elements, and Se is a third coating layer element. The first coating layer is coated on the surface of the primary particles and secondary particles of the nickel-based positive electrode material matrix, the second coating layer is coated on the first coating layer, and the third coating layer is coated on the second coating layer. The positive electrode material is tested by XPS, the average valence state of the surface nickel is 2.67; the 2θ angle position difference of the 108 and 110 peaks in the XRD diffraction pattern is 0.41°; in the in-situ XRD test, the cell change rate in the c-axis direction during the charging process is 2.88%.

[0035] (1) A nickel-cobalt-manganese hydroxide precursor Ni 0.93 Co 0.03 Mn 0.04 (OH)2, lithium monohydrate are added into a high-speed mixing stirrer in a molar ratio of 1:1.05, stirred at a speed of 1000 rpm for 30 min, then heated to 500℃ at a heating rate of 3℃ / min in a box furnace with an oxygen concentration ≥96%, and then heated to 745℃ for 12 h, and then naturally cooled to room temperature, crushed, and sieved through a 300 mesh sieve to obtain a primary sintered material; (2) The primary sintered material and Co(OH)2 are added into a high-speed mixing stirrer in a molar ratio of 1:0.02, stirred at a speed of 1000 rpm for 30 min, then heated to 650℃ at a heating rate of 3℃ / min in a box furnace under an oxygen atmosphere, and then naturally cooled to room temperature, sieved through a 300 mesh sieve to obtain a secondary sintered material; (3) A 0.03 mol / L NaAlO2 solution is prepared with water, and the pH value is 11.78. The primary sintered material obtained in step (1) is washed with the NaAlO2 solution for 3 min, the solid-liquid mass ratio of the washing is 0.9, the temperature of the deionized water for washing is controlled at 8℃, the stirring rate is 700 rpm, after washing, the sample is placed in a vacuum oven and vacuum dried at 160℃ for 6 h, then naturally cooled to room temperature, and sieved through a 300 mesh sieve to obtain a water-washed product; (4) The water washing product and SeO2 were added into a high-speed mixing blender at a molar ratio of 1:0.002, stirred at a speed of 1000 rpm for 30 min, then heated to 250°C at a heating rate of 3°C / min in a box furnace under an oxygen atmosphere, kept for 6 h, naturally cooled to room temperature, sieved through a 300-mesh screen to obtain a nickel-based positive electrode material.

[0036] The surface lithium carbonate content of the nickel-based positive electrode material was 0.105%, the lithium hydroxide content was 0.486%, and the lithium to transition metal ratio Li / Me was 1.003.

[0037] Comparative Example 1: The nickel-based positive electrode material of the present comparative example was Li 1.00 Ni 0.93 Co 0.03 Mn 0.04 B 0.01 O2, and the preparation method comprises: (1) The nickel-cobalt-manganese hydroxide precursor Ni 0.93 Co 0.03 Mn 0.04 (OH)2 and lithium monohydrate were added into a high-speed mixing blender at a molar ratio of 1:1.05, stirred at a speed of 1800 rpm for 30 min, then heated to 500°C at a heating rate of 3°C / min in a box furnace with an oxygen concentration of ≥96%, kept for 2 h, then heated to 745°C and kept for 12 h, naturally cooled to room temperature, crushed, and sieved through a 300-mesh screen to obtain a primary sintered material; (2) The primary sintered material obtained in step (1) was washed with deionized water for 3 min, the solid-liquid mass ratio of the washing was 1.0, the temperature of the deionized water for washing was controlled at 8°C, the stirring rate was 700 rpm, after washing, the sample was placed in a vacuum oven and vacuum dried at 160°C for 6 h, then naturally cooled to room temperature, and sieved through a 300-mesh screen to obtain a water washing product; (3) The water washing product and boric acid were added into a high-speed mixing blender at a molar ratio of 1:0.01, stirred at a speed of 1000 rpm for 30 min, then heated to 300°C at a heating rate of 3°C / min in a box furnace under an oxygen atmosphere, kept for 6 h, naturally cooled to room temperature, and sieved through a 300-mesh screen to obtain a nickel-based positive electrode material.

[0038] Comparative Example 2: The nickel-based positive electrode material of the present comparative example was Li 1.00 Ni 0.91 Co 0.05 Mn 0.04 B 0.01 O2, and the preparation method comprises: (1) The nickel-cobalt-manganese hydroxide precursor Ni0.93 Co 0.03 Mn 0.04 (OH)2, lithium hydroxide monohydrate is added into a high-speed mixing blender in a molar ratio of 1:1.05, stirred at a speed of 1800 rpm for 30 min, then heated to 500℃ at a heating rate of 3℃ / min in a box furnace with an oxygen concentration of ≥96%, and kept for 2 h, then heated to 745℃ and kept for 12 h, naturally cooled to room temperature, crushed, and sieved through a 300 mesh sieve to obtain a primary sintered material; (2) The primary sintered material and Co(OH)2 are added into a high-speed mixing blender in a molar ratio of 1:0.02, stirred at a speed of 1000 rpm for 30 min, then heated to 650℃ at a heating rate of 3℃ / min in a box furnace under an oxygen atmosphere, kept for 8 h, naturally cooled to room temperature, sieved through a 300 mesh sieve to obtain a secondary sintered material; (3) The secondary sintered material obtained in step (2) is washed with deionized water for 3 min, the solid-liquid mass ratio of the washing is 1.0, the temperature of the deionized water for washing is controlled at 8℃, the stirring rate is 700 rpm, after washing, the sample is placed in a vacuum oven and vacuum dried at 160℃ for 6 h, then naturally cooled to room temperature, and sieved through a 300 mesh sieve to obtain a washed product; (4) The washed product and boric acid are added into a high-speed mixing blender in a molar ratio of 1:0.01, stirred at a speed of 1000 rpm for 30 min, then heated to 300℃ at a heating rate of 3℃ / min in a box furnace under an oxygen atmosphere, kept for 6 h, naturally cooled to room temperature, and sieved through a 300 mesh sieve to obtain a nickel-based positive electrode material.

[0039] Comparative Example 3: The nickel-based positive electrode material of this comparative example is Li 1.00 Ni 0.91 Co 0.05 Mn 0.04 Na 0.01 Al 0.01 B 0.01 O2, and the preparation method comprises: (1) A nickel-cobalt-manganese hydroxide precursor Ni 0.93 Co 0.03 Mn 0.04 (OH)2, lithium hydroxide monohydrate is added into a high-speed mixing blender in a molar ratio of 1:1.05, stirred at a speed of 1800 rpm for 30 min, then heated to 500℃ at a heating rate of 3℃ / min in a box furnace with an oxygen concentration of ≥96%, and kept for 2 h, then heated to 745℃ and kept for 12 h, naturally cooled to room temperature, crushed, and sieved through a 300 mesh sieve to obtain a primary sintered material; (2) The primary sintered material and Co(OH)2 were added into a high-speed mixing blender at a molar ratio of 1:0.02, stirred at a speed of 1000 rpm for 30 min, then heated to 650°C at a heating rate of 3°C / min in a box furnace under an oxygen atmosphere, and kept at 650°C for 8 h, naturally cooled to room temperature, and sieved through a 300-mesh sieve to obtain a secondary sintered material; (3) A 0.3 mol / L NaAlO2 solution was prepared, the secondary sintered material obtained in step (2) was washed with the NaAlO2 solution for 3 min, the solid-liquid mass ratio of the washing was 0.9, the temperature of the deionized water used for washing was controlled at 8°C, the stirring rate was 700 rpm, after washing, the sample was placed in a vacuum oven and vacuum dried at 160°C for 6 h, then naturally cooled to room temperature, and sieved through a 300-mesh sieve to obtain a washed product; (4) The washed product and boric acid were added into a high-speed mixing blender at a molar ratio of 1:0.01, stirred at a speed of 1000 rpm for 30 min, then heated to 300°C at a heating rate of 3°C / min in a box furnace under an oxygen atmosphere, and kept at 300°C for 6 h, naturally cooled to room temperature, and sieved through a 300-mesh sieve to obtain a nickel-based positive electrode material.

[0040] Performance test: The electrochemical performance of the positive electrode materials in the above examples and comparative examples was studied using a CR2032 button cell.

[0041] Positive electrode sheet: The positive electrode materials of Examples 1-3 and Comparative Examples 1-3, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) were stirred and dispersed with a solvent NMP at a mass ratio of 92.5:5:2.5, coated on an aluminum foil substrate, and roll-pressed to obtain a positive electrode sheet.

[0042] Negative electrode sheet: A lithium metal sheet.

[0043] Electrolyte: A 1 mol / L LiPF6 solution, a mixed solvent of EC and DMC at a ratio of 1:2, and an additive of 1% VC.

[0044] The CR2032 button cell was assembled for battery testing, with a charge cutoff voltage of 4.3 V and a discharge cutoff voltage of 3.0 V.

[0045] The following are the test results of the electrical performance of the positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-3. The test results of the electrical performance are shown in Table 1.

[0046] Table 1: Test results of the electrical performance of the positive electrode materials in Examples 1-3 and Comparative Examples 1-3

[0047] As can be seen from Table 1, the nickel-based positive electrode material prepared in Examples 1-3 not only has a simple preparation method, but also can significantly improve the first discharge capacity, has lower impedance, and can significantly improve the high-temperature cycle performance, to a great extent, solves the common problem of the destruction of the surface of the high-nickel material by water washing, resulting in large impedance and poor cycle performance. Comparative Example 1 does not adopt the alkali washing and three-layer coating design in the application, the surface structure is destroyed after water washing, lithium is precipitated from the crystal lattice, the polarization impedance is relatively large, and the overall electrochemical performance is poorer than that of the examples. In Comparative Example 2, the alkali washing and wet coating in the application are not adopted, the surface structure is destroyed after water washing, although dry coating is performed, the surface structure cannot be repaired, the surface is still a lithium-deficient structure, and the electrochemical performance is still poorer than that of the examples. In Comparative Example 3, the concentration of the alkali solution is not controlled, the coating layer on the surface of the substrate is relatively thick after water washing, the capacity is lower, and the impedance is larger than those of the examples.

Claims

1. A nickel-based positive electrode material, characterized by, The nickel-based positive electrode material substrate and three layers of coating layers, the first coating layer is coated on the surface of the primary particles and secondary particles of the nickel-based positive electrode material substrate, the coating element includes a fourth period variable valence transition metal element; the second coating layer is coated on the surface of the first coating layer, the coating element includes at least one of Li, Na, K and Al; the third coating layer is coated on the surface of the second coating layer, and the coating agent is an oxide with a melting point <700℃.

2. The nickel-based positive electrode material of claim 1, wherein, The nickel-based positive electrode material is tested by X-ray photoelectron spectroscopy, and the average valence of the surface Ni element is +2.6 to +2.9; the nickel-based positive electrode material has a 2θ angle position difference of 108 and 110 peaks in the X-ray diffraction pattern of ≥0.25°; during the charging process, the in-situ X-ray diffraction test shows that the cell change rate Δc / c max ≤4%, wherein Δc is the change value of the cell parameter c, Δc=c max -c min .

3. The nickel-based positive electrode material of claim 1, wherein, The coating element of the first coating layer includes at least one of V, Mn, Fe, Co and Ni; the coating element of the third coating layer includes at least one of B, Se, Co, Mn, Sb and V; the mass of the first coating layer is 0.5%-3% of the mass of the nickel-based positive electrode material substrate, the mass of the second coating layer is 0.01%-0.2% of the mass of the nickel-based positive electrode material substrate, and the mass of the third coating layer is 0.1%-1% of the mass of the nickel-based positive electrode material substrate.

4. The nickel-based positive electrode material of claim 1, wherein, The chemical formula of the nickel-based positive electrode material matrix is Li z Ni 1-x-y Co x M y O2, wherein M is at least one of Mn and Al, 1.0≤z≤1.03, 0≤x≤0.2, and 0≤y≤0.

2.

5. The nickel-based positive electrode material according to any one of claims 1 to 4, characterized in that, The surface lithium carbonate content of the nickel-based positive electrode material is ≤0.3%, the lithium hydroxide content is ≤0.6%, and the lithium to transition metal ratio Li / Me = 1.0-1.

01.

6. A method for producing the nickel-based positive electrode material according to any one of claims 1 to 5, characterized by, The method comprises the following steps: S1, mixing a nickel-based hydroxide precursor and a lithium source, and then performing sintering treatment to obtain a primary sintered product; S2, mixing the primary sintered product in step S1 with a first coating agent, and then performing sintering treatment after mixing to obtain a secondary sintered product; S3, preparing a second coating agent into an alkali solution, and then performing water washing on the secondary sintered product in step S2 with the alkali solution, and then drying to obtain a water-washed product; S4, mixing the water-washed product in step S3 with a third coating agent, and then performing sintering treatment after mixing to obtain a nickel-based positive electrode material.

7. The preparation method according to claim 6, characterized in that, In step S1, the lithium source includes at least one of lithium hydroxide, lithium carbonate and lithium nitrate, the molar ratio of lithium in the lithium source to the nickel-based hydroxide precursor is (1.03-1.08):1; the nickel-based hydroxide precursor is a nickel-cobalt-manganese, nickel-cobalt-aluminum or nickel-cobalt-manganese-aluminum hydroxide precursor; in step S2, the coating element of the first coating agent includes at least one of V, Mn, Fe, Co and Ni; in step S4, the coating element of the third coating agent includes an oxide of at least one of B, Se, Co, Mn, Sb and V.

8. The preparation method according to claim 6, characterized in that, In step S1, the sintering treatment includes two-stage sintering, the sintering temperature of the first-stage sintering is 450-600℃, the holding time is 2-5h, the sintering temperature of the second-stage sintering is 600-800℃, and the holding time is 8-20h; in step S2, the sintering temperature of the sintering treatment is 500-700℃, and the holding time is 4-10h; in step S4, the sintering temperature of the sintering treatment is 300-700℃, and the holding time is 4-10h; the sintering atmosphere is an oxygen-containing atmosphere with an oxygen concentration ≥96%.

9. The preparation method according to claim 6, characterized in that, In step S3, the second coating agent is an alkali liquor prepared from at least one of NaAlO2, Na2CO3, NaOH, LiOH and KOH; in the alkali liquor, the concentration c is 0.01-0.2 mol / L, the pH value is 10-13, and the solubility s at 20℃ is greater than 1 g / 100 g water; the water washing temperature is 5-25℃, the water washing solid-liquid mass ratio is 0.5-3.0, and the stirring speed during water washing is 400-900 rpm / min.

10. The method of claim 9, wherein, Before water washing, the surface lithium carbonate content t of the secondary sintered product is 0.3%-0.6%, the lithium hydroxide content h is 0.3%-0.8%, the solute relative molecular mass of the alkali liquor is M, and the maximum concentration cmax of the alkali liquor is [1-100l(t-0.1%) / 1.43-100l(h-0.3%) / 10.8]×10s / M.